Das abfallrechtliche Anlagengenehmigungsverfahren in Japan: Lösungsansätze zur Formalisierung des informellen Vorverfahrens - Walkling, Julia (Zeitschrift für Japanisches Recht, 2006)
Obtaining the necessary official approval for setting up waste disposal facilities is usually complex and time-consuming. The promoters of such undertakings regard these procedures as a serious obstacle for their investments. Neighbors of such entities, on the other hand, are concerned that their interests are not sufficiently taken care of. This conflict exists in Japan as well as in Germany and poses a specific challenge for the regulatory authorities in both countries which can hardly be dealt with by the traditional regulatory instruments. This is where administrative guidance comes into the picture in the form of seemingly non-binding contacts between the authorities and the promoters well before the official legal approval procedures start. In Germany, administrative theory did not take notice of this specific form of administrative action until the early 1980s. In Japan, however, it has been established as part of Japanese administrative law since Meiji times. Since the 1960s, certain forms of informal administrative action have been summarized under the term gyôsei shidô, which normally is translated as “administrative guidance.” If one looks at the approval proceedings for factories with an impact on the environment in Japan and Germany, one finds in both countries similar informal actions before the official administrative proceedings start. Before filing the complete application with the pertinent authorities, the promoter usually contacts the authorities on an informal level, asking for information and help to guarantee a successful approval proceeding. The parties involved discuss the necessary documentation, legal requirements, and the probable chances of a successful completion of the proceeding. It is then that the basic structural decisions for the proceedings are agreed upon between the authority and the promoter. This informal proceeding helps to speed up and simplify the subsequent official proceedings. Furthermore, it creates the possibility to include or integrate third parties concerned by the project into the approval proceedings. This in turn helps to ease conflicts of interest between the promoters and future neighbors of the planned factory. This kind of compromise was of special relevance in Japan, because until 1997 the official approval proceedings for waste disposal facilities did not grant any right of procedural participation for concerned citizens. Informal administrative proceedings were an integral part of the approval proceedings in both countries, but for a considerable time they were not regulated by law. Thus mistakes happened that were caused by a lack of transparency and equal treatment in the course of administrative action. As a reaction to this, both Japan and Germany took appropriate steps to institutionalize informal proceedings for the sake of reducing inherent legal dangers. Both countries now have specific regulations as part of the approval proceedings for waste disposal facilities. In Japan, the pertinent provision is Art. 15 IV-VI of the Waste Disposal Law and in Germany § 71 c II of the Administrative Procedure Law as well as § 2 Abs. II of the 9th Ordinance to the Federal Pollution Law. The article discusses the Japanese solution and its development in the context of the administrative approval proceedings for waste disposal facilities. This is followed by an evaluation and then contrasted with the law-based German solution for a comparison of both legal regimes. Finally, the author discusses whether the Japanese insights can be used to improve the pertinent German legal regime. (English translation by the Editors)